Incidence of Peripheral Nerve Injury Incidence among Patients Suffering from Oral and Maxillofacial Trauma - Tahmasub Faraz Tayyab, Abdul Wali Khan, Syeda Rabia Rahat Geelani, Muhammad Adnan Akram, Ammara Anwar, Zeeshan Aslam Jan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the peripheral nerve injury incidence among patients suffering from oral and maxillofacial trauma. Method: This cross-sectional study was conducted in Department of Oral and Maxillofacial Surgery, Ayub Teaching Hospital, Abbottabad. Sample was of 187 patients, and data was collected using non- probability, Consecutive sampling technique. Results: The findings showed that the age range of 10% patients was between 10-20years, age range of 40% patients was between 21-30years, age range of 32% patients was between 31-40years, and age range of 18% patients was >40years. The mean value of age of total sample was 31.21 ± 7.01. Males were 86% and females were 14% of entire sample. Trigeminal nerve injury was found in 35% patients whereas facial nerve injury was found in 16% patients. Conclusion: The study concludes that the peripheral nerve injury incidence was 35% (trigeminal nerve injury) of oral trauma while in maxillofacial trauma (facial nerve injury) 16% in our setup.